THE EFFECT OF INFLATION ON FIRM PROFITABILITY: AN APPLICATION IN RETAIL SECTOR OF BORSA ISTANBUL - DAYI, Faruk (Suleyman Demirel University Visionary Journal, 2020)
The cost of sales increases together with an increase in inflation. The firms that aims to reach a profit target, reflect the cost increases on prices. Increases in prices may be higher than those in costs. Increasing prices lead to inflation. The firms in Turkey experienced a sudden increase in the exchange rates in the period of July-September 2018, and used this depreciation as an excuse for increasing their prices. However, even those firms that were slightly affected by the increase in the exchange rates did so. The aim of the study is to determine the effect of inflation due to the increase in the exchange rates on firm profitability. The study sample consists of ten retail trade firms traded at the Borsa Istanbul equity market. Earnings, cost of sales, gross profit, operating profit and net profit data for Q2-Q3 of 2017 and 2018 are used. A paired sample t-test is conducted to determine the variables’ change between 2017 and 2018 periods. The findings indicate that the variables do not change significantly from 2017 to 2018. Variables are also analyzed by using percentage method. The results show that the supermarket firms’ profits are higher than the increases in their costs.
Keywords: Enflasyon,Maliyet,Kâr,Perakende Sektörü,Finansal Analiz; Inflation,Cost,Profit,Retail Sector,Financial Analysis; 8. Economic growth